The Mavi Marmara Incident and the Blockade in Armed Conflict Viewed from the Perspective of Human Rights and International Humanitarian Law - Toban, Musa Purna; Sochfan, Achmad; Widiarto, Asrof (AGUSPATI Research Institute, 2024)
— The Gaza Freedom Flotilla, established on May 31, 2010, aims to provide humanitarian aid to the Gaza Strip, Palestine, by breaking through the Israeli naval blockade. This humanitarian mission delivers essential daily supplies to the people of Gaza using three passenger ships and six cargo ships. One of the three passenger ships is Mavi Marmara, which carried 700 humanitarian activists from 37 countries. While the Gaza Freedom Flotilla was sailing in international waters (73 miles from the coast towards Gaza), Israeli forces attacked the Mavi Marmara. This attack sparked protests from the global community. Meanwhile, Israeli Prime Minister Benjamin Netanyahu justified the actions of the Israeli forces as necessary for national security enforcement. To this day, the Israeli assault on the Mavi Marmara has not received any sanctions from the UN, leading to an indirect understanding that there is a justification for Israel's defence efforts for its territorial security. The ongoing conflict between Israel and Palestine is the reason for the Israeli blockade of the Gaza Strip, which aims to prevent weapon smuggling by Hamas. The blockade has severely impacted the people of Gaza, resulting in shortages of food, clean water, and medicine. This blockade has faced significant criticism from the international community due to its humanitarian impact on the residents of Gaza